Soccer-specific reactive repeated-sprint ability in elite youth soccer players: Maturation trends and association with various physical performance tests - Di Mascio, M.; Ade, J.; Musham, C.; Girard, O.; Bradley, P. S. (The Journal of Strength and Conditioning Research, 2020)
Repeated-sprint ability is an important physical prerequisite for competitive soccer and deviates for players in various stages of growth and development. Thus, this study investigated reactive repeated-sprint ability in elite youth soccer players in relation to maturation (age at peak height velocity) and its association with performance of other physical tests. Elite male youth players from an English Premier League academy (U12, n = 8; U13, n = 11; U14, n = 15; U15, n = 6; U16, n = 10; and U18, n = 13) completed the reactive repeated-sprint test (RRST; 8 × 30-m sprints with 30-second active recovery), and other physical tests including the Yo-Yo intermittent recovery test level 2 (Yo-Yo IR2), arrowhead agility test, countermovement jump test with arms (CMJA), in addition to 10- and 20-m straight-line sprints. Reactive repeated-sprint test (RRST) performance (total time across 8 sprints) progressively improved from U12 to U16 (p < 0.01; effect size [ES]: 1.0-1.9), yet with no differences found between U16 and U18. No between-group differences in RRST performance were evident after accounting for age at peak height velocity (p > 0.05; ES: <0.3). Correlation magnitudes between performance on the RRST and other tests were trivial to moderate for the Yo-Yo IR2 (r = -0.15 to 0.42), moderate to very large for the arrowhead agility test (r = 0.48-0.90), moderate to large for CMJA (r = -0.43 to 0.66), and trivial to large for 10- and 20-m sprints (r = 0.05-0.61). The RRST was sensitive at tracking maturation trends in elite youth players, although performance improvements were not as marked from 15 to 16 years of age. RRST performance correlates with several physical qualities decisive for competitive soccer (agility, speed, power, and aerobic endurance).